Quality Characteristics of instant Noodles made from Flour Composites of Modified Potato Starch, Mocaf Flour and Wheat Flour with the addition of phospate salt - Rini Hardiyanti; Herla Rusmarilin; Terip Karo-Karo (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Noodles were usually made from wheat flour. Wheat is Indonesia imported commodity that due to limited stock, it can cause problems in food security. In order to solve the problems, food diversification is done by replacing noodle raw materials with potato starch. This study was done using Heat Moisture Treatment red potato starch to make instant noodle mixed with mocaf flour and wheat flour with different comparisons and 4 type of phosphate salts.The research was conducted in three phase i.e the manufacture of natural starch, modified by Heat Moisture Treatment (HMT) and then testing the physical and chemical characteristics of the modified potato starch HMT included moisture content, ash content, oil and water absorption, dextrose equivalent (DE), total sugar, reducing sugar, the degree of polymerization (DP), the clarity of paste, amilograph with rapid viscoanalizer, starch granules form and whiteness. Phase three was making noodles from composite flour and moisture content, ash content, protein content, fat content, fiber content, carbohydrate content, water absorption power, percent elongation, cooking loss, color scores before and after cooking, organoleptic test for aroma and flavor were tested. Composition of modified potato starch, mocaf flour and wheat flour of 15%:40%:45% with Sodium Tripoly Phospate respectively produced the best instant noodles.   Keywords: Potato, HMT modified starch, mocaf flour, wheat flour,  phosphate salt, instant noodles